The paneth cell distribution of the small intestine of the rats at postnatal periods - Nejdet Şimşek; Hasan Hüseyin Dönmez (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine Paneth cell distribution in Ihe crypts ot different regions of small intestine of rats at postnatal period. Tlnrtysix Wislar Albino rats were used in the investigation. The rats were divided into 0, 15. 30, 90, 180 and 365 day-old-age groups and sacrificed by cervical dislocation. In order lo determine the Paneth cell co-unis in ihe crypts of the duodenum, jejunum and ileum regions of the small intestine, tissue samples were fixed in Bouin's solution, prepared blocks in paraftine and sectioned. The sections were stained with phyloxine-iartrazine. Paneth cell count of each animal as determined by counting 2400 crypts in each section and the data were subjected to statistical analysis. Paneth cells were not found at the first 15 day of poslnatal period, Paneth cell number per crypt was higher in 30-day- old rals than those of 90. 180 and 365-day- old rats. The number of Ihe cells in ihe duodenum of mature rats decreased as rats matured. However, there was no significant changes in the cell numbers of the ileum and jejunum ol the rats from different age groups.